MANAGING COLLABORATION IN THE 21ST CENTURY - A GLOBAL PERSPECTIVE - Carmen Valentina RĂDULESCU; Ildiko IOAN (Revista de Management Comparat International)
Recent studies underline the rethinking of the innovation model. The traditional approach, based on the creation of new ideas in a centralized Research – Development department and the implementation of results at small scale isn’t at 21st century’s level anymore. This research paper will present the innovation that is brought to market through networks of niche companies, with unique capabilities that operaște in an organized way. This new model requires from the companies the development of different skills and the ability to collaborate with business partners for the creation of innovational synergy. There are some less-inspired approaches of the issue, like: the approach focused on cutting costs (underestimating the strategic role of worldwide communication/collaboration); the approach of collaboration in an inefficient way (one way relationship) and the suboptimal capitalization of cooperation opportunities (direct translation to globally connected companies). In antithesis, companies situated at the peak of the innovation hierarchy develop strategies for the globalization of communication and collaboration for performance and to create new business opportunities.